Poor glycaemic control: prevalence, factors and implications for the care of patients with type 2 diabetes in Kinshasa, Democratic Republic of the Congo: a cross-sectional study - Fina Lubaki, Jean-Pierre; Omole, Olufemi Babatunde; Francis, Joel Msafiri (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction Diabetes is a significant problem in sub-Saharan Africa and achieving glycaemic control poses a health challenge among patients living with type 2 diabetes. There are limited data on glycaemic control in Kinshasa, Democratic Republic of the Congo. This study assessed the prevalence and factors associated with glycaemic control to inform potential interventions to improve glycaemic control in Kinshasa. Methods This was a cross-sectional study conducted between November 2021–September 2022 among patients recruited from 20 randomly selected health facilities in Kinshasa. Participants were asked to complete a structured questionnaire and to provide two millilitres of blood for Hb1AC assay. Poor glycaemic control was defined as HbA1c ≥7%. Univariate and multivariable logistic regressions were performed to identify factors associated with poor glycaemic control. Results A total of 620 participants were recruited for this study. Study participants had a median age of 60 (IQR=53.5-69) years with the majority being female (66.1%), unemployed (67.8%), having income below the poverty line (76.4%), and without health insurance (92.1%). About two-thirds of the participants (420; 67.6%) had poor glycaemic control. Participants on monotherapy with insulin (AOR=1.64, 95%CI [1.10-2.45]) and those on a treatment duration ≥7 years (AOR=1.45, 95%CI [1.01-2.08]) were associated with increased odds of poor glycaemic control while being overweight (AOR= 0.47, 95%CI [0.26-0.85]) and those with uncontrolled blood pressure (AOR=0.65, 95% CI [0.48-0.90]) were protective for poor glycaemic control. Conclusion Poor glycaemic control is prevalent among patients with type 2 diabetes in Kinshasa, DRC. Being on insulin alone and a duration of diabetes treatment equal or more than 7 years predisposed to poor glycaemic control. By contrary, having uncontrolled blood pressure and being overweight had protective effect against poor glycaemic control. These links between uncontrolled blood pressure and overweight on the one hand, and glycaemic control on the other are unusual. These reflect, among other things, the specific characteristics of diabetes in sub Saharan Africa.